Stock Market Reaction to Product Innovation : Evidence from UK and Japan Major Car Manufacturer - Fong, Kok Seng (2005)
This study examines the impact of product innovation through the launch of concept vehicles which is offspring of product innovation based on the automobile industry using the widely accepted event study methodology. The automobile industry was selected because of its economics importance and its reliance on constant product innovation to create shareholder value. Hypotheses were formulated to test the impact of the events and the results from the hypothesis testing using parametric method suggest that the impact on the launch of concept vehicles do not have sufficient impact on the firm’s share returns. However, exceptional cases are noted to occur and in the study there have been mixed result gathered from the parametric and non parametric test, As such there was insufficient evidence to make a generalisation that product innovation would increase firm value base on the evidence which was gathered. Therefore, case by case examinations were required to form a conclusion.